2005
DOI: 10.1158/0008-5472.can-04-3441
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the Arachidonic Acid Pathway and Peroxisome Proliferator–Activated Receptor Ligands Have Superadditive Effects on Lung Cancer Growth Inhibition

Abstract: Arachidonic acid (AA) metabolizing enzymes and peroxisome proliferator-activated receptors (PPARs) have been shown to regulate the growth of epithelial cells. We have previously reported that exposure to the 5-lipoxygenase activating protein-directed inhibitor MK886 but not the cyclooxygenase inhibitor, indomethacin, reduced growth, increased apoptosis, and up-regulated PPARA and ; expression in breast cancer cell lines. In the present study, we explore approaches to maximizing the proapoptotic effects of PPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 46 publications
4
57
0
Order By: Relevance
“…In our previous works (22,26), we showed biochemically that MK886 causes nuclear translocation of PPARg. This transcription factor is thought to be a tumor suppressor, and this translocation occurs within the first 2 hours postexposure.…”
Section: Discussionmentioning
confidence: 74%
“…In our previous works (22,26), we showed biochemically that MK886 causes nuclear translocation of PPARg. This transcription factor is thought to be a tumor suppressor, and this translocation occurs within the first 2 hours postexposure.…”
Section: Discussionmentioning
confidence: 74%
“…Seven of the nine showed significant inhibition by a pooled t test. Among these nine completely blocked genes were arachidonate 5-lipoxygenaseactivating protein (Alox5ap), urokinase plasminogen activator (Plaur) and osteopontin (Spp1/Opn), already shown to be involved in driving tumor promotion and progression (29)(30)(31)(32). Despite the P value of 0.062, the inhibition of TPA-induced Opn mRNA expression by TAM67 was confirmed by quantitative PCR (Table 1), showing about 15-fold inhibition.…”
Section: Resultsmentioning
confidence: 96%
“…Arachidonic acid release is hypothesized to mediate cell spreading, adhesion, or proliferation in macrophages and cancer cells (Teslenko et al, 1997;Avis et al, 2005). Furthermore, PLA 2 activity is hypothesized to mediate the release of arachidonic acid during these events (Guthridge et al, 1994;Longo et al, 1999), and some studies have suggested roles for iPLA 2 (Shen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%